If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 5x = -5 Solving -10 + 5x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = -5 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = -5 + 10 5x = -5 + 10 Combine like terms: -5 + 10 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| -5x-9=4n+2 | | 8-5y=80 | | 120x^4-60x^3=0 | | 19h+4h-22h-h+h=12 | | 2(9/5) | | -x-1=-2x+4 | | -12x^3+6x^2+6x=0 | | 3x-15=4x-8 | | -7p-14=-2+p+11 | | 8x-5=80 | | 4-45/9*5-6 | | 7x+10=10x-20 | | 8x=3(x)^(1/2) | | (4,-3)=3/5 | | -4(3y+8)= | | 1.3x+1.5=0.3+0.7 | | 9x-6=10x-4 | | 120x^4=60x^3 | | 4x^3-28x^2-400x+700=0 | | 1=2x+16 | | y=-1/3(-2)-1 | | q=40+5 | | 5x-9=4x+18 | | y=-1/3(2)-1 | | 34=-11+m | | y=-1/3(4)-1 | | (11/12)x=1/3 | | 18+18+18+9= | | y=2+16 | | 0.6x-1=-0.5x-0.7 | | x-2/5=1-x/2 | | (-2x+35)=(6x+3) |